The impact of deans’ distributed leadership on university teachers’ job performance: the mediating role of job satisfaction - Hua Yu; Aida Hanim A. Hamid; Jamalul Lail Abdul Wahab; Mohd Izwan Mahmud (Cogent Education)
This study investigates how deans’ distributed leadership influences university teachers’ job performance in Jiangsu, China, emphasizing the mediating role of job satisfaction. A structured questionnaire survey collected data from 470 university teachers, and the hypotheses were analyzed using Structural Equation Modeling (SEM). The results demonstrate that distributed leadership significantly enhances teachers’ job satisfaction and job performance through four dimensions: organizational empowerment, collaborative decision-making, teacher participation, and resource support. Furthermore, mediation analysis confirms that job satisfaction partially mediates the relationship between distributed leadership and job performance, highlighting both direct and indirect effects. These findings underscore the critical role of distributed leadership in fostering a supportive and participative environment that boosts teachers’ performance. The study contributes to the theoretical understanding of distributed leadership while offering practical implications for university administrators, such as promoting participatory leadership practices and providing professional resources to enhance job performance and educational outcomes.